O bonde passou : videoclipes de funk ostentação e o mercado musical brasileiro na Internet - Belo, Rafaela Freitas (2016)
The research aims to analyze the release of videoclips from artists of ostentation funk from the formal and market perspective to understand the place that cultural object - the ostentation funk - occupies in Brazilian popular music field today and how their production logic and media coverage from the uses of video clips on the web establishes alternative models of integration in the cultural industry, for after the success to be appropriate by the larger music industry. The research analyzes the ostentation funk field through the success of videoclips released by MC Gui and MC Guimê, artists who have achieved great repercussion on YouTube and are also characterized by having gained ground in other media, especially TV and radio. From the historical background in the course of work, we understand that the funk that emerged in Rio de Janeiro arrived in São Paulo and was adapted to the rap amid a backdrop of expanding middle class, economic development, larger access to the internet, professionalization of agents, emergence of video editing tools that have facilitated user interface and rise of social networking, creating the ostentation funk on the outskirts of Brazil's largest metropolis. The ostentation funk is housed in a mainstream musical circulation system and is part of the structures of pop music, through the success of videoclips available on the Internet, but also it's part of an independent scenario with artists who produce and publish their own work. The research concludes that the videoclip is essential for the popularization of ostentation funk, through the dynamics of movement and dissemination of videos on YouTube and there is a rapprochement with US rappers through clothing, the theme and the objects present in the videoclips